Analisis Yuridis Eksistensi Hukum Homoseksual dalam Peraturan Perundang-Undangan Indonesia - Putri, Lorena Andrea; Budimansyah, Afriyadi; Hotimah, Husnul; Dienullah, Muhamad Dhava; Buana, Vaddeli Bagas; Febrianti, Yenny (Indonesian Journal of Law and Justice, 2023)
This research examines the existence of homosexual laws within the framework of legal regulations in Indonesia. The close relationship between law and human rights (HAM) is the main focus, with the issue of homosexuality causing divisions in society. In the context of human rights, universal principles emphasize that every individual has the same rights without discrimination. However, laws and regulations in Indonesia do not yet provide clear guidance regarding the existence of homosexuals. This results in divisions in society. This research uses a normative juridical method with a regulatory and conceptualization approach. The results show that the 1945 Constitution of the Republic of Indonesia and Law of the Republic of Indonesia no. 39 of 1999 concerning Human Rights recognizes human rights without discrimination, but must be in line with religious values, morality and law. Marriage arrangements in Indonesia emphasize marriage as a bond between a man and a woman, based on the principle of belief in one Almighty God. The legalization of same-sex marriage raises various problems, including conflict with religious norms and a decline in birth rates. In the context of criminal law, the spread of ideology that is contrary to Pancasila can be subject to sanctions. Therefore, the movement to legalize homosexuality in Indonesia may face legal obstacles. Indonesian National Work Competencies in the Field of Forensic Audit.Forensic Audit.